Analysis of on-board wireless sensor network as an alternative to traditional wired network - S. V. Kuznetsov (Научный вестник МГТУ ГА)
Wireless networks based on the principle and technology of Wireless Avionics Intra-Communications (WAIC), that is, wireless avionics or wireless onboard intercom are becoming increasingly widespread on modern aircraft. The development and deployment of WAIC on board is a complex task, as its solution is directly related to ensuring safety of flights. It requires preliminary careful scientific analysis. The article analyzes the on-board wireless sensor network as an alternative to a traditional wired network using the example of a short-haul aircraft. A rough estimate of the length of the electrical harness connecting the sensors of the aircraft systems with the electronic units is carried out in order to determine the possible gain in the length of the wires when switching to a wireless sensor network (WSN). To solve this problem, the aircraft sensors of each aircraft system are placed on a large-scale grid; for each sensor, analyze the feeder circuits by the composition of the plug connectors, the number of occupied contacts and the length of wires for each contact to the corresponding electronic unit. It is shown that the heterogeneous sensor system of the aircraft with wireless sensors can reduce the number of wires by about 1200, the length of the wires of the feeder network by about 15 km. The most promising aircraft systems in terms of switching to wireless sensors are: fuel system (about 3400m), fire equipment system (about 1300m) and hydraulic system (about 1300m). Further scientific research is required to make an informed decision about the technical feasibility and advisability of using a wireless sensor network for each specific aircraft system.